Comparative Study Of Financial Behavior Of College Students In Southeast Asia - Paul Usmany; Fitri Novilia; Ani Pujiati; Rieneke Ryke Kalalo; Agnes Soukotta (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
In measuring the good or bad financial behavior of each student sampled through an online questionnaire, researchers measured it using the smart PLS 4.0 analysis tool with the standard that the higher the influence of student Financial Behavior in each country that is the object of research influences Investment Decisions, the better the Financial Behavior of a student (Sugiyono 2019). This research is a quantitative research with an explanatory approach, namely an approach that makes previous research the spearhead in building argument construction in the article being worked on (Jonathan Sarwono 2016) & (Abdurahman 2016). The data used in this study are primary data that researchers obtained through the distribution of online questionnaires with the same 10 questions for each student who was the object of the sample in the three countries.